Adoption, usage, and global impact of broadband technologies : diffusion, practice, and policy - Dwivedi, Yogesh Kumar (Information Science Reference, 2010)
"This book provides a comprehensive coverage of broadband deployment, diffusion, adoption, usage, and policies as they have been realized by research in many countries around the world"--Provided by publisher.